PENGARUH LEVERAGE DAN KUALITAS AUDIT TERHADAP NILAI PERUSAHAAN DENGAN KEAHLIAN KOMITE AUDIT SEBAGAI VARIABEL MODERATING (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2012 – 2016) - Tjandra Dewi; Anis Chariri (Diponegoro Journal of Accounting, 2018)
Firm value can reflect the value of assets owned by companies such as securities, one of which is the stock. For companies that issue shares in the capital market, the stock price traded on the stock exchange is an indicator of the company's value.This study aims to obtain empirical evidence and analyze the influence of leverage, and audit quality on firm value, also the audit committee's expertise in moderating leverageand audit quality relationship with firm value. The population in this study is the manufacturing companies registered in Indonesia Stock Exchange in 2012 – 2016. The total sample used in this study was 199 companies based on established criteria.Data analysis was done by descriptive statistic analysis, classical assumption test, and hypothesis test. The results of this research analysis indicate that the leverage doesn’t have a significant effect on firm value, while the audit quality has a significant positive effect on firm value. Then, the audit committee's expertise can’t moderate the leverage and audit quality relationship with firm value.